Characteristics of hemoglobin and its pro‐oxidative activity in washed silver carp (Hypophthalmichthys molitrix) mince as affected by pH. Issue 6 (10th May 2021) - Javed, Miral; Yu, Wumei; Yang, Hong; Xiong, Shanbai; Liu, Youming
Abstract: The objectives of this study were to investigate the pro‐oxidative activity of hemoglobin and its effect on lipid and protein oxidation changes in silver carp washed mince over 12 days of storage at 4°C under different pHs (6.0, 6.5, 7.0, 7.5, 8.0). The results suggested that the formation of Methemoglobin decreased the relative oxygenation of hemoglobin in acidic pH (6, 6.5) as compared to neutral or alkaline pH (7, 7.5, and 8.0). Hemoglobin promoted lipid oxidation more effectively under acidic conditions (pH 6.0) rather than alkaline pH (8.0), as indicated by the higher peroxide values and thiobarbituric acid‐reactive substances. Moreover, hemoglobin was found to be more conducive in initiating protein oxidation by increasing the carbonyl and dimeric tyrosine content while decreased the total sulfhydryl content in washed mince system under acidic conditions, which was linked to a higher auto‐oxidation rate. These results suggested that the lipid and protein oxidation in fish mince were more likely mediated by hemoglobin, whose pro‐oxidative activity could be influenced by its pH level. Practical applications: This study demonstrates that hemoglobin pro‐oxidative activity is mainly affected by pH. The shift of pH from acidic to alkaline could attenuate hemoglobin autoxidation. This work provides a means to slow down lipid and protein oxidation during storage of fish mince by adjusting to slightly alkaline pH, which could maintain the freshwater fish mince quality.